Virtual Lab Based on STEM Approach: Is It Effective to Enhance Students Concept of Temperature and Heat? - Syukri, Muhammad; Rahmi, Mulia; Saminan, Saminan; Artika, Wiwit; Subramaniam, Tamil Selvan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
This study aims to create a virtual lab in science-physics learning based on a valid, practical, and effective STEM-based virtual lab for junior high school students. The research was conducted using Research and Development.The research was conducted at SMP Negeri Unggul Tunas Nusa (junior high school). This research was carried out in the even semester of the 2021/2022 academic year. The subjects used in this study were students of class VII Tusa at SMPN Unggul Tunas Nusa in the academic year 2021/2022, totaling 29 students. The sampling technique used is random sampling. Based on the analysis, the average percentage assessment of all aspects is 87.89%, meaning the STEM-based virtual lab product is very feasible. The STEM-based virtual lab is assessed for teachers' and students' use. Practical criteria for teachers and students. The pretest means of student learning outcomes scored 24.57, while the posttest means after being applied to a STEM-based virtual lab scored 84.45. The average score of N-gain student learning outcomes is 0.80, which is high and able to improve student learning outcomes.The results of this study are expected to be used as an alternative for a teacher to improve student learning outcomes.